Spirit Pluralisme dalam Klenteng Sam Po Kong Semarang - Julianto, Edi Nurwahyu (Universitas Semarang, 2015)
Klenteng Sam Po Kong has very deep meaning as a symbol of multi cultural; multi ethnic and multi religious. Klenteng Sam Po Kong has a different function, not only used by people with background religious Tri Dharma (Budha, Tao and Konghuchu), but also used by Javanese ethnic with different religious backgrounds. Between ethnic China and Java, mutual respect and tolerance run beliefs and rituals of each. More over, Klenteng Sam Po Kong is a form of pluralism which reflected the fact Sino Javanese Muslim Culture is preserved to date both of sightings physical culture and system cultural in the form of religious rites performed by ethnic China and Java.